The Relationship Between Scientific Process Skills and Science Achievement: A Meta-Analysis Study - sevda dolapcioglu; Münevver Subası (Universitas Pendidikan Indonesia, 2022)
One of the main challenges in science education is interpreting existing studies to improve scientific process skills. The main purpose of this study is to bring together the quantitative findings obtained on the relationship between scientific process skills and academic achievement in science education, to highlight the relevant gaps in 5838 samples, and to interpret the overall effect size. The bibliographic research was carried out through the ERIC and ProQuest databases, especially in the Science Education Research category. Two hundred thirty-four articles published between 2005 and 2020 were obtained. Following the application of the inclusion criteria, 18 articles were selected according to the random-effects model, resulting in an average effect size of 0.56. Two moderator variables with a significant correlation between science achievement and scientific process skills were analyzed (Q = 417.082; df = 17; p .05; I2 = 95.22). The percentage of the moderator variables explaining the relationship was interpreted by meta-regression analysis. Educational inferences have shown a requirement for further research at the high school and university levels on the relationship between science method skills and scientific achievement.